Percutaneous Coronary Intervention vs Coronary Artery Bypass Grafting in Patients With Left Main Coronary Artery Stenosis - Jonathan, Jonathan; Ronald, Ronald (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the management of left main coronary artery disease (LMCAD) through percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) reveals a complex interplay of efficacy, safety, and long-term outcomes. The introduction of advanced technologies, particularly drug-eluting stents (DES), has positioned PCI as a viable alternative to CABG, even in cases traditionally managed by surgical intervention. Literature Review: The findings from (Eifert et al., 2010) indicate a significant increase in the acceptance of PCI, with long-term survival rates being comparable to CABG in both single and multivessel cases. However, concerns arise regarding the higher rates of recurrent symptoms and the necessity for repeat operations following PCI, which may question its long-term efficacy, particularly in the context of LMCAD. Conclusion: In conclusion, the body of literature supports the notion that both PCI and CABG are viable treatment options for LMCAD, with each approach offering distinct advantages and limitations. The decision-making process should be individualized, taking into account patient-specific factors, including age, comorbidities, and the anatomical complexity of coronary lesions. Ongoing research and longer follow-up studies are essential to further elucidate the long-term implications of these interventions and to refine clinical guidelines for the management of LMCAD.